Antagonistic test of Beauveria bassiana fungus in suppressing Collectotrichum spp. in vitro - Dini Puspita Yanti; Dwi Aninditya; Irmalia Fitri Siregar (CIB Nusantara, 2025)
Chili plants (Capsicum sp.) are widely cultivated in Indonesia because they have high marketing value in terms of consumption and economy. The purpose of this study was to determine the ability of various types of B. bassiana herbs to suppress Colletotrichum spp. in vitro. This study used a completely randomized design (CRD) consisting of 6 treatments and 5 replicates. The treatments used are as follows: A = No Treatment (Control), B = B. bassiana isolate BbKo, C = B. bassiana isolate TD, D = B. bassiana isolate WS, E = B. bassiana isolate PD, F = B. bassiana isolate KT2B21. The parameters observed were fungal inhibition using the bunch culture method and the volatile test (vapor culture method). B. bassiana fungus has the ability to inhibit the growth of Colletotrichum spp. fungi in vitro. B. bassiana BbKo has the highest inhibitory ability of 50.30%. B. bassiana isolate PD has the highest colony area of 69.70 cm2.